Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2341/13-221-c
|View full text |Cite
|
Sign up to set email alerts
|

Three-year Clinical Evaluation of Different Restorative Resins in Class I Restorations

Abstract: Except for the better marginal adaptation that packable resin composite showed, siloranebased restorative, nanofilled resin, and packable resin composite resulted in similar clinical performance in restoring Class I cavities after 3 years. SUMMARYThe aim of the present study was to evaluate the three-year clinical performance of a nanofilled resin composite, a packable resin composite, and silorane-based resin restorations in Class I occlusal cavities. Twenty-eight patients with at least three similar-sized oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 21 publications
3
19
2
Order By: Relevance
“…There is currently no consensus about the bonding performance of the silorane adhesive system. Some studies found that silorane adhesive system showed equal performance with conventional methacrylate-based adhesives [3638]. However our study is in line with the others that found lower bond efficiency [18, 39].…”
Section: Discussionsupporting
confidence: 91%
“…There is currently no consensus about the bonding performance of the silorane adhesive system. Some studies found that silorane adhesive system showed equal performance with conventional methacrylate-based adhesives [3638]. However our study is in line with the others that found lower bond efficiency [18, 39].…”
Section: Discussionsupporting
confidence: 91%
“…Fifteen studies evaluated marginal adaptation after 12 months, with one study [ 17 ] presenting three experimental groups, and another [ 40 ] two experimental groups, totaling 18 experimental groups ( Fig 4 ). Among the 18 groups, 12 presented results that favored the control group (conventional composite), [ 19 , 25 , 27 , 28 , 30 , 33 , 34 , 37 , 40 , 41 ] two that favored the experimental group (resins with modified monomers) [ 32 , 35 ], one that did not favor any of the groups, since results were similar for both groups [ 29 ], two presented no marginal adaptation alterations in both groups [ 17 , 26 ], and one study reported that all restorations in both groups demonstrated some sort of marginal adaptation alteration [ 38 ]. Meta-analysis demonstrated that at the 12-month follow-up assessment, the overall effect of methacrylates-based composite resins was significantly better than the ormocer, silorane and bulk-fill composites (p = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Nanofills have also been demonstrated to behave very similarly in vitro to nano- and micro-hybrids, both in terms of mechanical properties and depth of cure [35, 36]. Clinical studies with follow up times of up to 5 years have demonstrated an annual failure rate for nanofilled composites of less than 3%, deeming these materials clinically acceptable and within the range of survival of micro- and nano-hybrid materials [3739]. …”
Section: The Evolution Of Filler Systemsmentioning
confidence: 99%